A informação geográfica voluntária e o planejamento urbano: abordagem sobre a utilização das vias urbanas em Guarapuava-PR - TOLEDO, BRUNO HENRIQUE COSTA (2016)
This study arises from the possibility of measuring the transformations of the urban space, by means of digital information collected by several volunteers during their activities relating to the daily movement. From these data it is possible to assign new uses related to space, conditioned to their origin formation, which is modified by new socio spatial dynamics that the informational society creates. The volunteered geographic information enters on scene to subsidies this analysis, in addition to contributing to the space planning. The study still searches relate the use of volunteered geographic information with the urban space and planning, select the study areas of agreement with this, in addition to propose a methodology for using such information within the geotechnologies, mainly of geographic information systems. Volunteers Data as be used to represent the sports practices: race and cycling in urban tracks, was also performed an analysis of these spaces, besides proposing guidelines for your planning. Through the verification and analysis of urban tracks, one may conclude that the volunteered geographic information has great usefulness in planning of urban space, with data which create new spatial readings and allow manifestation of a new geographic intelligence, allowing a global and voluntary participation for a better understanding of the use of spaces related to the city, scene of our different ways of life.